The instability mechanisms and precursor information of different type rocks based on acoustic emission. - Ruixiong Xue; Yinghui Kong; Jinxiang Feng (PLoS ONE)
This study presented the results of indoor uniaxial compression and acoustic emission (AE) monitoring tests for five type rocks: marble, granite, siltstone, sandstone and limestone. The experiment adopted a displacement-controlled loading method with a loading rate of 0.18mm/min, and AE monitoring was carried out synchronously. Some AE parameters were obtained. Detailed analysis of AE parameters RA and AF values revealed the evolutionary laws of the RA/AF value distribution range and rock failure mechanisms for five different type rocks; The models of damage types inside rocks over time had been established. Furthermore, the microseismic parameter lgN/b was introduced. Analyzing the lgN/b values dynamic change process revealed the instability laws, and rock instability precursor information was obtained. The results showed that an increase in the proportion of shear cracks, along with a wider range of the RA/AF values distribution can serve as precursor information for rock instability. Before rock failure occurred, the lgN/b values consistently increased. Additionally, the study found that the change laws of lgN/b values can reveal the extent of development of intrinsic weak structures inside the rocks. Through a multi-parameter and multi-method comprehensive analysis, we can more scientifically identify the instability precursor information of different type rocks in terms of time, and the hierarchical warning was achieved. The research results can provide a reference for microseismic monitoring at various sites and establish certain scientific basis for effective on-site warning strategies.